Re-irradiation for oligo-recurrence from esophageal cancer with radiotherapy history: a multi-institutional study - Keiichi Jingu; Yuzuru Niibe; Hideomi Yamashita; Kuniaki Katsui; Toshihiko Matsumoto; Tomohiro Nishina; Atsuro Terahara (Radiation Oncology, 2017)
Abstract Background Neoadjuvant chemoradiotherapy following surgery has recently become a standard therapy. The purpose of the present study was to determine the effectiveness and toxicity of re-irradiation for oligo-recurrence in lymph nodes from esophageal cancer treated by definitive radiotherapy or by surgery with additional radiotherapy. Methods We reviewed retrospectively 248 patients treated with (chemo)radiotherapy for oligo-recurrence in lymph nodes from esophageal cancer in five Japanese high-volume centers between 2000 and 2015. Thirty-three patients in whom re-irradiation was performed were enrolled in this study, and the results for patients in whom re-irradiation was performed were compared with the results for other patients. Results Median maximum lymph node diameter was 22 mm. Median total radiation dose was 60 Gy. The median calculated biological effective dose using the LQ model with α/β = 10 Gy (BED10) in patients in whom re-irradiation was performed was significantly lower than the median BED10 in others. There was no different factor except for BED10, histology and irradiation field between patients with a past irradiation history and patients without a past irradiation history. The median observation period in surviving patients in whom re-irradiation was performed was 21.7 months. The 3-year overall survival rate in the 33 patients with a past irradiation history was 17.9%, with a median survival period of 16.0 months. Overall survival rate and local control rate in patients with a past irradiation history were significantly worse than those in patients without a past irradiation history (log-rank test, p = 0.016 and p = 0.0007, respectively). One patient in whom re-irradiation was performed died from treatment-related gastric hemorrhage. Conclusions Results in the present study suggested that re-irradiation for oligo-recurrence in lymph nodes from esophageal cancer treated by definitive radiotherapy or by surgery with additional radiotherapy might be acceptable but unsatisfactory.